RETRACTED : The Influence of Work Conflict, Job Stress and Work Discipline on The Employees’ Performance of PT. Pelindo II – IPC Jakarta - Ghafar Ibnu Tsalis; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aimed to analyze the effects of job stress work conflict and work discipline on the performance of employees of PT. Pelindo II-IPC Jakarta in 2016. The results of research using primary data in the form of a questionnaire to 100 respondents in PT. Pelindo II-IPC Jakarta in 2016 showed that there is influence between Conflict Work, Work Stress and Work Discipline on employee performance PT. Pelindo II-IPC Jakarta. This is evidenced by F count larger than F table and t greater than t table. The results of calculations based on t test obtained t for Conflict Work (X1) of 10.386 and thitung for Work Stress (X2) is 5,918 bigger than t table 1.660, meaning that the work conflict and work stress and significant positive effect on employee performance of PT Pelindo II. While thitung for Work Discipline (X3) of 1.178 is smaller than 1,660, which means ttabel Discipline had no effect on employee performance of PT Pelindo II. While the regression model as follows Y = 0,571X1 + 0,383X2 + 0,080X3 This suggests that the three independent variables X1, X2, and X3 affect the Y.